2014
DOI: 10.1590/1678-457x.6406
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological and sensory evaluation of a bioactive food blend

Abstract: The potential of functional foods to decrease the risks of chronic non-communicable diseases has motivated the development of products with beneficial effects on fat and carbohydrate metabolism. The present study aimed at analyzing the physicochemical, microbiological, and sensory properties of a bioactive food blend developed to help the nutritional therapy provided to hypolipidemic and hyperglycemic patients with HIV/AIDS treated with antiretroviral therapy. The food blend was evaluated for moisture, protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Previous results indicate that BFC exerts an antiatherogenic effect on glycemic control and reduces triglycerides [ 9 , 10 ], which is probably due to its chemical composition, its high linolenic acid, soluble fibers and isoflavone contents, and the benefits observed in this study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous results indicate that BFC exerts an antiatherogenic effect on glycemic control and reduces triglycerides [ 9 , 10 ], which is probably due to its chemical composition, its high linolenic acid, soluble fibers and isoflavone contents, and the benefits observed in this study.…”
Section: Discussionsupporting
confidence: 55%
“…Database”), there were few changes: 20 more participants in the expected sample amount and inclusion of one more study variable, the Conicity Index. Regarding the bromatological, microbiological and sensory analysis of the BFC and the lipid profile after consumption have already been published in other manuscripts [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Ferreira et al [36], who reported the nutritional quality indexes found in the BFC, showed the efficacy of fatty acids with respect to the reduction of atherogenic and thrombogenic events, since the compound contains flaxseed in its formulation. The significant reduction in LDL-C levels and total cholesterol levels is due to the functionality of fatty acids and soluble fiber, which act primarily in reducing atherogenic cholesterol, decreasing the deposition of atheroma in vein walls and arteries, thus preventing cardiovascular events, and consequently, factors associated with metabolic syndrome [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…BFC is rich in proteins, in PUFAs (60.41%) (n-3 series (30%) and n-6 series (27%)) and also in dietary fibers. Among such fiber it is possible to find soluble fibers including lignan and β-glucans, both with high viscosity and fermentable potential ( 107 ). Moreover BFC has been studied as adjuvant therapy in the NCDs directly related to metabolic syndrome (MS) including atherosclerosis.…”
Section: Functional Foods As Gut Microbiota Modulators and Chemoprevementioning
confidence: 99%